RELASI GENDER PEREMPUAN DALAM TEKS LA GALIGO - Hasmawati SU; Ery Iswary; Prasuri Kuswarini (LPPM Institut Pendidikan Nusantara Global, 2023)
This research is qualitative, using the descriptive method. This study aims to analyze the gender relations of women in the La Galigo text based on NBG 188 Volume 3 using equilibrium theory. This study uses library research methods. The results of the research show that women's gender relations are developed equally, where women are not only involved and have a role in domestic affairs but also in the public. Things that are generally done by men are also done by women. For example, women can express opinions and make decisions regarding their household lives. Women are given the trust to do things that are usually done by men; even women can give orders as well as men.